Prevalence and determinants of stillbirths in Dilokong Hospital of the Limpopo Province - Dibakwane, Lesibe Portia (My University, 2022)
Background: Stillbirth rates are a health problem and they cause distractions in the families. There are more than 5 million perinatal deaths occurring each year, ending preventable stillbirths and neonatal deaths continues to form a significant part of the international public health agenda beyond 2015. There are several risk factors which are associated with stillbirths and this could be classified as maternal, foetal and external risk factors. Therefore, the focus of the study was on the prevalence and determinants of stillbirths in Dilokong Hospital of the Limpopo Province. Methods: A retrospective descriptive study was conducted which followed a quantitative approach. This study used secondary data from patient clinical records from the maternity ward in Dilokong Hospital. Comparison between groups for continuous and categorical variables was performed using student t-test, and chisquare test, respectively. P-value less than 0.05 at 95% confidence level was regarded as significant. Findings: The prevalence of stillbirth amongst women who delivered at Dilokong hospital between period 2016 and 2019 was 13.5 % (CI: 0.12 – 15.2). The prevalence of stillbirth is stratified by year and it shows that highest prevalence was in 2018 at 42.5% followed by 2017, 2019 and 2016 at 23.2%, 19.7% and 14.6 respectively. The prevalence of stillbirth increased with increasing maternal age from 0.4% in the age group ≤14 years to 26.2% then decreased to 21.5% in the age group 30 – 34 years. The prevalence of macerated stillbirth between period 2016 and 2019 was 11.0%, for fresh stillbirth was 2.6 %. There was significant association of age, marital status of pregnant women, level of education, parity, gravidity, syphilis and HIV status. Older women at age 18 years and above were 1.4 times more likely to have stillbirth and 1.9 times more likely to have fresh stillbirth at p<0.05. Single women were 3.3 times more likely to have stillbirth and 3 times more likely to have macerated stillbirth as compared to married women. Fresh stillbirth was not significantly associated with marital status of pregnant women. Educational level was significantly associated with both stillbirth and macerated stillbirth as those women with no education or having primary educational level were 12.3 times more likely to have stillbirth and 14 times more likely to have macerated stillbirth as compared to women with tertiary educational level. vi Women who had pregnancies that have each resulted in the birth of an infant capable of survival (parity) for four or more times were 2.4 times more likely to have stillbirth and women who were in their fifth or more pregnancies (gravida) were 1.8 times more likely to have stillbirth and 3 times more likely to have fresh stillbirth. Lastly, women who had tested positive for syphilis were 4.1 times more likely to have stillbirth and 3.7 times more likely to have macerated stillbirth and women who were HIV positive were 3.1 times more likely to have stillbirth and 2.3 times more likely to have macerated stillbirth. CONCLUSION: The prevalence of stillbirth was very high in the current study and there is a need for studies on stillbirth and related factors in rural areas of Limpopo Province. This study showed that maternal age, low educational level, marital status of pregnant women, high parity, gravidity, syphilis and HIV status were statistically associated with stillbirth. The factors associated with stillbirth in the current study are preventable if quality focused antenatal care, intrapartum care is provided. Therefore, identification of pregnancy complications and facilitation of proper method of delivery is key to improve quality of care. Efforts to reduce unacceptably high stillbirth in the current study are needed. This study recommends that pregnant mothers need to be educated about the dangers in pregnancy and importance of antenatal visits.
Thesis (MPH.) -- University of Limpopo, 2022
Keywords: Stillbirths; Macerated; Fresh stillbirths; Prevalence; Maternal risk factors; Perinatal death; Stillbirth; Newborn infants -- Mortality; Health facilities; Hospitals